2002
DOI: 10.1046/j.1471-4159.2002.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Profound molecular changes following hippocampal slice preparation: loss of AMPA receptor subunits and uncoupled mRNA/protein expression

Abstract: The acute hippocampal slice preparation is a convenient, in vitro model widely used to study the biological basis of synaptic plasticity. Although slices may preserve their electrophysiological properties for several hours, profound molecular changes in response to the injury caused by the slicing procedure are likely to occur. To determine the magnitude and duration of these changes we examined the post-slicing expression kinetics of three classes of genes known to be implicated in long-term synaptic plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 77 publications
(119 reference statements)
2
29
1
Order By: Relevance
“…5 and data not shown). Other investigators have shown that c-fos mRNA is induced after slice preparation (Taubenfeld et al, 2002) but that this is uncoupled from translation. Thus, the amount of protein produced is low, and protein levels are not sufficient to overcome tissue autofluorescence and remain undetectable.…”
Section: Slice Recording From Neurons Activated By In Vivo Manipulationmentioning
confidence: 97%
“…5 and data not shown). Other investigators have shown that c-fos mRNA is induced after slice preparation (Taubenfeld et al, 2002) but that this is uncoupled from translation. Thus, the amount of protein produced is low, and protein levels are not sufficient to overcome tissue autofluorescence and remain undetectable.…”
Section: Slice Recording From Neurons Activated By In Vivo Manipulationmentioning
confidence: 97%
“…One possibility is suggested by evidence that the preparation of the slice causes transient increases in the activity of kinases involved in synaptic plasticity (Ho et al, 2004) followed by a return to conditions closer to those found in vivo. In parallel there is surge in the expression of transcriptional regulators (Taubenfeld et al, 2002;Zhou et al, 1995) and synaptic proteins. Thus, it is possible that at least some of the proteins necessary for consolidation are present at supra normal levels in freshly prepared slices, thereby creating an artificial condition in which inhibitors are ineffective.…”
Section: Incubation Time Determines the Effect Of Protein Synthesis Imentioning
confidence: 99%
“…Otherwise, the discrepancy may be ascribable to differences in sample preparations. It has been reported that slicing can cause drastic changes in synapses (Kirov et al, 1999) and loss of GluR1 and GluR3 proteins (Taubenfeld et al, 2002) in the hippocampus. In addition, we cannot exclude the possibility that immunoreactive AMPARs may be partly nonfunctional, although our previous data suggested a close correlation between number of functional AMPAR channels and immunogold particles in immature CF-PC synapses (Tanaka et al, 2005).…”
Section: All Synapses Have Amparmentioning
confidence: 99%